Development and characterization of new borate-based compounds for X-rays, gamma rays and neutron luminescence dosimetry - França, Leonardo Vinícius da Silva (2022)
Radiation dosimetry is required in several contexts, such as X-ray imaging, nuclear medicine, radiotherapy, radiation-exposed research facilities, synchrotrons and space, to name a few. In view of this, a technique based on the optically stimulated luminescence (OSL) phenomenon, which is the light emission of a previous irradiated material when optically stimulated, has emerged. After more than 20 years of research, there are only two commercially available OSL dosimeters, which are based on Al2O3 :C and BeO compounds. The main objective of this work is to propose new OSL phosphors based on a calcium borate compound, i.e., CaB6O10 (Zeff=11.5) doped with lanthanides (Gd3+, Tb3+ or Ce3+) and silver (Ag+ ). Tb,Ag-doped compound, for instance, exhibited OSL sensitivity comparable to that of Al2O3 :C (using U340 Hoya filters), wide linear dose-range with no signs of saturation (30 mGy up to 20 Gy), fading of ~30% after 24 h following stability, neutron sensitivity, and showed to be reproducible and repeatable. Gd,Ag-doped compound exhibited similar dosimetric features. OSL from different compounds exhibited luminescence lifetimes ranging from microsecond to nanosecond time-scale, depending on the dopant used. This addresses both 2D laser scanning dosimetry and pulsed OSL dosimetry requirements using the same host compound.